Synergizing Customary Law and Religious Moderation in the Societal Life of Tigawasa Village, Buleleng, Bali - Enok Risdayah; Paryati; Jujun Junaedi; Wakidul Kohar; Asep Iwan Setiawan; Rohmanur Aziz; Barzan Faizin (Khazanah Hukum, 2026)
This article discusses the process of integration between customary law as a system of local norms and religious moderation as a national policy in Tigawasa Village, Bali. The study is grounded in Talcott Parsons’ structural functionalism theory, particularly the four AGIL functions (adaptation, goal attainment, integration, and latency), to analyze the ongoing social dynamics. Customary law in Tigawasa not only plays a role in preserving tradition but also demonstrates the ability to adapt to national values such as tolerance, non-violence, and openness to diversity. Meanwhile, religious moderation is not imposed as a coercive policy but is embraced as a value transmitted through local cultural channels. The study finds that the function of adaptation is reflected in the capacity of customary law to respond to new values; goal attainment is evident in the shared commitment to maintaining harmony; integration is realized through the role of local actors in fostering social cohesion; and latency is sustained through intergenerational socialization. These findings suggest that the integration between customary law and religious moderation can proceed harmoniously when both are functionally appreciated within the social system. Therefore, Tigawasa Village can serve as a model for strengthening community-based religious moderation.